Effects of helmet nonuse and seating position on patterns and severity of injuries in child motorcycle passengers - Hsiu-Ping Fan; Wen-Ta Chiu; Mau-Roung Lin (BMC, 2019)
Abstract Background A prospective study was conducted to investigate the effects of helmet nonuse and seating position on patterns and severity of motorcycle injuries among child passengers in Taiwan. Methods In total, 305 child passengers aged ≤14 years who visited the emergency departments of three teaching hospitals following a motorcycle crash were recruited. Children's injury data were collected from medical records, and their riding behaviors along with operators' demographics were sourced from telephone interviews. Parental responses over the telephone about children's riding behaviors were checked by roadside observations. Results Results of the multivariable logistic regression analysis revealed that compared to child passengers aged ≥7 years, those aged ≤3 (odds ratio (OR), 2.88; 95% confidence interval (CI), 1.37~6.06) and 4~6 years (OR, 2.93; 95% CI, 1.50~5.70) were significantly more likely to have sustained a head/face injury, while those aged 4~6 years (OR, 2.76; 95% CI, 1.01~7.55) were significantly more likely to have sustained a severe injury. Compared to child passengers who were wearing a full-coverage helmet, those who were not wearing a helmet were significantly more likely to have sustained a head/face injury (OR, 3.12; 95% CI, 1.02~9.52) and a severe injury (OR, 3.02; 95% CI, 1.19~7.62). Children seated in front of the operator were significantly more likely to have experienced a head/face injury (OR, 2.22; 95% CI, 1.25~3.94) than those seated behind the operator. For each increment in the riding speed of 1 km/h, the odds of a severe injury to child passengers increased by 5% (OR, 1.05; 95% CI, 1.01~1.09). Conclusions For the safety of child motorcycle passengers, laws on a minimum age restriction, helmet use, an adequate seating position, and riding speed need to be enacted and comprehensively enforced.